Step
*
1
4
1
1
of Lemma
Legendre-differential-equation
1. n : ℕ
2. λx.r0 ∈ (-∞, ∞) ⟶ℝ
3. λx.r1 ∈ (-∞, ∞) ⟶ℝ
4. ¬(n = 0 ∈ ℤ)
5. ¬(n = 1 ∈ ℤ)
6. f1 : (-∞, ∞) ⟶ℝ
7. g1 : (-∞, ∞) ⟶ℝ
8. f : (-∞, ∞) ⟶ℝ
9. g : (-∞, ∞) ⟶ℝ
10. x : ℝ
11. v : ℝ
12. Legendre(n - 1;x) = v ∈ ℝ
13. v1 : ℝ
14. Legendre(n - 2;x) = v1 ∈ ℝ
15. v2 : ℝ
16. (f x) = v2 ∈ ℝ
17. v3 : ℝ
18. (g x) = v3 ∈ ℝ
19. v4 : ℝ
20. (f1 x) = v4 ∈ ℝ
21. v5 : ℝ
22. (g1 x) = v5 ∈ ℝ
23. m : {2...}
24. n = m ∈ {2...}
25. y : ℝ
26. (r1 - x * x) = y ∈ ℝ
27. (((y * v4) - (r(2) * x) * v5) + (r((m - 2) * (m - 1)) * v1)) = r0
28. (((y * v2) - (r(2) * x) * v3) + (r((m - 1) * m) * v)) = r0
29. (y * v3) = ((r(m - 1) * v1) - (r(m - 1) * x) * v)
⊢ (((y * ((2 * m) - 1 * ((x * v2) + v3) + v3 - m - 1 * v4)/m) - (r(2) * x)
* ((2 * m) - 1 * (x * v3) + v - m - 1 * v5)/m)
+ (r(m * (m + 1)) * ((2 * m) - 1 * x * v - m - 1 * v1)/m))
= r0
BY
{ Assert ⌜(((y * ((2 * m) - 1 * ((x * v2) + v3) + v3 - m - 1 * v4)) - (r(2) * x)
          * ((2 * m) - 1 * (x * v3) + v - m - 1 * v5))
          + (r(m * (m + 1)) * ((2 * m) - 1 * x * v - m - 1 * v1)))
          = r0⌝⋅ }
1
.....assertion..... 
1. n : ℕ
2. λx.r0 ∈ (-∞, ∞) ⟶ℝ
3. λx.r1 ∈ (-∞, ∞) ⟶ℝ
4. ¬(n = 0 ∈ ℤ)
5. ¬(n = 1 ∈ ℤ)
6. f1 : (-∞, ∞) ⟶ℝ
7. g1 : (-∞, ∞) ⟶ℝ
8. f : (-∞, ∞) ⟶ℝ
9. g : (-∞, ∞) ⟶ℝ
10. x : ℝ
11. v : ℝ
12. Legendre(n - 1;x) = v ∈ ℝ
13. v1 : ℝ
14. Legendre(n - 2;x) = v1 ∈ ℝ
15. v2 : ℝ
16. (f x) = v2 ∈ ℝ
17. v3 : ℝ
18. (g x) = v3 ∈ ℝ
19. v4 : ℝ
20. (f1 x) = v4 ∈ ℝ
21. v5 : ℝ
22. (g1 x) = v5 ∈ ℝ
23. m : {2...}
24. n = m ∈ {2...}
25. y : ℝ
26. (r1 - x * x) = y ∈ ℝ
27. (((y * v4) - (r(2) * x) * v5) + (r((m - 2) * (m - 1)) * v1)) = r0
28. (((y * v2) - (r(2) * x) * v3) + (r((m - 1) * m) * v)) = r0
29. (y * v3) = ((r(m - 1) * v1) - (r(m - 1) * x) * v)
⊢ (((y * ((2 * m) - 1 * ((x * v2) + v3) + v3 - m - 1 * v4)) - (r(2) * x) * ((2 * m) - 1 * (x * v3) + v - m - 1 * v5))
+ (r(m * (m + 1)) * ((2 * m) - 1 * x * v - m - 1 * v1)))
= r0
2
1. n : ℕ
2. λx.r0 ∈ (-∞, ∞) ⟶ℝ
3. λx.r1 ∈ (-∞, ∞) ⟶ℝ
4. ¬(n = 0 ∈ ℤ)
5. ¬(n = 1 ∈ ℤ)
6. f1 : (-∞, ∞) ⟶ℝ
7. g1 : (-∞, ∞) ⟶ℝ
8. f : (-∞, ∞) ⟶ℝ
9. g : (-∞, ∞) ⟶ℝ
10. x : ℝ
11. v : ℝ
12. Legendre(n - 1;x) = v ∈ ℝ
13. v1 : ℝ
14. Legendre(n - 2;x) = v1 ∈ ℝ
15. v2 : ℝ
16. (f x) = v2 ∈ ℝ
17. v3 : ℝ
18. (g x) = v3 ∈ ℝ
19. v4 : ℝ
20. (f1 x) = v4 ∈ ℝ
21. v5 : ℝ
22. (g1 x) = v5 ∈ ℝ
23. m : {2...}
24. n = m ∈ {2...}
25. y : ℝ
26. (r1 - x * x) = y ∈ ℝ
27. (((y * v4) - (r(2) * x) * v5) + (r((m - 2) * (m - 1)) * v1)) = r0
28. (((y * v2) - (r(2) * x) * v3) + (r((m - 1) * m) * v)) = r0
29. (y * v3) = ((r(m - 1) * v1) - (r(m - 1) * x) * v)
30. (((y * ((2 * m) - 1 * ((x * v2) + v3) + v3 - m - 1 * v4)) - (r(2) * x) * ((2 * m) - 1 * (x * v3) + v - m - 1 * v5))
+ (r(m * (m + 1)) * ((2 * m) - 1 * x * v - m - 1 * v1)))
= r0
⊢ (((y * ((2 * m) - 1 * ((x * v2) + v3) + v3 - m - 1 * v4)/m) - (r(2) * x)
* ((2 * m) - 1 * (x * v3) + v - m - 1 * v5)/m)
+ (r(m * (m + 1)) * ((2 * m) - 1 * x * v - m - 1 * v1)/m))
= r0
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  \mlambda{}x.r0  \mmember{}  (-\minfty{},  \minfty{})  {}\mrightarrow{}\mBbbR{}
3.  \mlambda{}x.r1  \mmember{}  (-\minfty{},  \minfty{})  {}\mrightarrow{}\mBbbR{}
4.  \mneg{}(n  =  0)
5.  \mneg{}(n  =  1)
6.  f1  :  (-\minfty{},  \minfty{})  {}\mrightarrow{}\mBbbR{}
7.  g1  :  (-\minfty{},  \minfty{})  {}\mrightarrow{}\mBbbR{}
8.  f  :  (-\minfty{},  \minfty{})  {}\mrightarrow{}\mBbbR{}
9.  g  :  (-\minfty{},  \minfty{})  {}\mrightarrow{}\mBbbR{}
10.  x  :  \mBbbR{}
11.  v  :  \mBbbR{}
12.  Legendre(n  -  1;x)  =  v
13.  v1  :  \mBbbR{}
14.  Legendre(n  -  2;x)  =  v1
15.  v2  :  \mBbbR{}
16.  (f  x)  =  v2
17.  v3  :  \mBbbR{}
18.  (g  x)  =  v3
19.  v4  :  \mBbbR{}
20.  (f1  x)  =  v4
21.  v5  :  \mBbbR{}
22.  (g1  x)  =  v5
23.  m  :  \{2...\}
24.  n  =  m
25.  y  :  \mBbbR{}
26.  (r1  -  x  *  x)  =  y
27.  (((y  *  v4)  -  (r(2)  *  x)  *  v5)  +  (r((m  -  2)  *  (m  -  1))  *  v1))  =  r0
28.  (((y  *  v2)  -  (r(2)  *  x)  *  v3)  +  (r((m  -  1)  *  m)  *  v))  =  r0
29.  (y  *  v3)  =  ((r(m  -  1)  *  v1)  -  (r(m  -  1)  *  x)  *  v)
\mvdash{}  (((y  *  ((2  *  m)  -  1  *  ((x  *  v2)  +  v3)  +  v3  -  m  -  1  *  v4)/m)  -  (r(2)  *  x)
*  ((2  *  m)  -  1  *  (x  *  v3)  +  v  -  m  -  1  *  v5)/m)
+  (r(m  *  (m  +  1))  *  ((2  *  m)  -  1  *  x  *  v  -  m  -  1  *  v1)/m))
=  r0
By
Latex:
Assert  \mkleeneopen{}(((y  *  ((2  *  m)  -  1  *  ((x  *  v2)  +  v3)  +  v3  -  m  -  1  *  v4))  -  (r(2)  *  x)
                *  ((2  *  m)  -  1  *  (x  *  v3)  +  v  -  m  -  1  *  v5))
                +  (r(m  *  (m  +  1))  *  ((2  *  m)  -  1  *  x  *  v  -  m  -  1  *  v1)))
                =  r0\mkleeneclose{}\mcdot{}
Home
Index